2009
DOI: 10.1007/s00586-009-1189-0
|View full text |Cite
|
Sign up to set email alerts
|

Plasma disc decompression for contained cervical disc herniation: a randomized, controlled trial

Abstract: Prospective case series studies have shown that plasma disc decompression (PDD) using the COBLATION SpineWand device (ArthroCare Corporation, Austin, TX) is effective for decompressing the disc nucleus in symptomatic contained cervical disc herniations. This prospective, randomized controlled clinical trial was conducted to evaluate the clinical outcomes of percutaneous PDD as compared to conservative care (CC) through 1 year. Patients (n = 115) had neck/arm pain [50 on the visual analog scale (VAS) pain scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(49 citation statements)
references
References 69 publications
1
47
1
Order By: Relevance
“…Three studies performed nucleoplasty Eur Spine J (2013) 22:87-95 89 procedure [12,16,17] which seem largely comparable. In five studies, an ACDF procedure (anterior cervical discectomy with fusion) was described and in one study the surgical procedure was an occipitocervical fusion [20].…”
Section: Description Of the Studiesmentioning
confidence: 99%
See 3 more Smart Citations
“…Three studies performed nucleoplasty Eur Spine J (2013) 22:87-95 89 procedure [12,16,17] which seem largely comparable. In five studies, an ACDF procedure (anterior cervical discectomy with fusion) was described and in one study the surgical procedure was an occipitocervical fusion [20].…”
Section: Description Of the Studiesmentioning
confidence: 99%
“…1). Six studies, four of which were CCTs, were identified which examined surgery versus non-surgical interventions in patients with radiculopathy [12][13][14][15][16][17]. Three studies, of which two CCTs, compared surgery versus nonsurgical interventions in myelopathy patients [18,19,20].…”
Section: Description Of the Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Percutaneous PDD (plasma disc decompression) might offer a disc-preserving method resolving pain in patients with a painful disc herniation, where conservative treatments failed. This method might also offer a possibility to preserve the different disc cell morphologies in the disc [48]. This paper shows that the different disc cell morphologies changes significantly with increasing radiological degeneration grade.…”
Section: Discussionmentioning
confidence: 95%